2019
DOI: 10.1063/1.5080753
|View full text |Cite
|
Sign up to set email alerts
|

An adiabatic superconductor 8-bit adder with 24kBT energy dissipation per junction

Abstract: Adiabatic quantum-flux-parametron (AQFP) logic is an energy-efficient superconductor logic family. In this paper, we conducted high-frequency operation and energy measurement of an AQFP circuit with more than 1,000 Josephson junctions in the experiment. We designed an 8-bit carry look-ahead adder (CLA) using AQFP gates and fabricated it using an advanced fabrication technology, the AIST 10 kA/cm 2 Nb high-speed standard process (HSTP). The correct operation of the 8-bit CLA was demonstrated at a 1-GHz clock fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 30 publications
0
32
0
2
Order By: Relevance
“…6 denote the energy-delay product (EDP) of each logic family. The two blue solid lines are for AQFP logic; one represents the EDP based on an 8-bit carry look-ahead adder with Jc = 10 kA/cm 2 [61] and the other represents the EDP based on a buffer with Jc = 2.5 kA/cm 2 [53]. AQFP logic can operate with much less energy dissipation than the other logic families, and furthermore, the energy dissipation is close to the thermodynamic and quantum limits, where the quantum limit corresponds to the Planck constant.…”
Section: Adiabatic Quantum-flux-parametron (Aqfp)mentioning
confidence: 99%
“…6 denote the energy-delay product (EDP) of each logic family. The two blue solid lines are for AQFP logic; one represents the EDP based on an 8-bit carry look-ahead adder with Jc = 10 kA/cm 2 [61] and the other represents the EDP based on a buffer with Jc = 2.5 kA/cm 2 [53]. AQFP logic can operate with much less energy dissipation than the other logic families, and furthermore, the energy dissipation is close to the thermodynamic and quantum limits, where the quantum limit corresponds to the Planck constant.…”
Section: Adiabatic Quantum-flux-parametron (Aqfp)mentioning
confidence: 99%
“…DICE provides a promising solution for these limitations by building complex computing from simple low gate-count nodes and making better use of cryogenic refrigerator volumes with its 3D scaling. It has been shown that 8-bit superconducting ALUs can operate at 5 Ghz with 1.4 aJ power dissipation [8]. Extrapolating this to a custom Super-DICE node, a chip with O(10 4 ) Josephson junctions operating at 5GHz would require roughly 10 nW per operation.…”
Section: Projectionsmentioning
confidence: 99%
“…The major advantage of AQFP is the remarkable energy efficiency potential. A latest work 10 analyzed the energy dissipation of an 8-bit AQFP adder and reported a 24 k B T energy dissipation per junction based on the physical test. This number indicates that AQFP technology is a promising candidate to build low-energy systems approaching Landauder’s limit 1114 .…”
Section: Introductionmentioning
confidence: 99%